2004
DOI: 10.1159/000079186
|View full text |Cite
|
Sign up to set email alerts
|

A One-Year Trial of In-Center Daily Hemodialysis with an Emphasis on Quality of Life

Abstract: Background/Aims: Hemodialysis is associated with acute changes in several physiologic factors. Previous studies have suggested significant clinical and quality of life (QOL) benefits of daily hemodialysis (DHD) compared with 3 times weekly hemodialysis (CHD). We conducted a prospective trial to evaluate the effects of switching chronic hemodialysis patients to in-center DHD for a 12-month period. Methods: There were no exclusion criteria. Patients received hemodialysis 6 times per week. The study set a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…An early study by Bonomini et al [35] in 1972 noted that in six patients who had uremic-type symptoms despite increasing the time on dialysis from 22 to 30 h per week, changing patients to short daily dialysis (3-4 h for 5 days per week) led to resolution of signs and symptoms of advanced uremia such as anorexia, amenorrhea, severe anemia, impotence, insomnia, polyneuropathy, pruritus and restless leg syndrome. Improvements in these symptoms of uremia, as well as in blood pressure control and left ventricular hypertrophy, were noted by other investigators in both Europe and North America [40,41,42,43]. …”
Section: More Frequent Hemodialysissupporting
confidence: 56%
“…An early study by Bonomini et al [35] in 1972 noted that in six patients who had uremic-type symptoms despite increasing the time on dialysis from 22 to 30 h per week, changing patients to short daily dialysis (3-4 h for 5 days per week) led to resolution of signs and symptoms of advanced uremia such as anorexia, amenorrhea, severe anemia, impotence, insomnia, polyneuropathy, pruritus and restless leg syndrome. Improvements in these symptoms of uremia, as well as in blood pressure control and left ventricular hypertrophy, were noted by other investigators in both Europe and North America [40,41,42,43]. …”
Section: More Frequent Hemodialysissupporting
confidence: 56%
“…Whereas the traditional cardiovascular risk factors do not account for the increased mortality in CKD patients (3,4), measures of mineral and bone disorders (MBD), including hyperphosphatemia, are associated with increased death risk (5)(6)(7)(8)(9). Hyperphosphatemia may be involved in the pathogenesis of vascular calcification (10)(11)(12). Hence, prevention and correction of hyperphosphatemia and dietary phosphorus burden are major components of the management of CKD.…”
mentioning
confidence: 99%
“…Nineteen studies met the inclusion criteria [4,5,7,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Three studies were excluded because the vascular access event rates were not reported [26,27] or because of missing demographic data [28].…”
Section: Resultsmentioning
confidence: 99%